Skattekonkurrence og EU's skattestruktur - Tommy Søndergaard Poulsen (University of Southern Denmark, Department of Environmental and Business Economics (IME), 2001)
Do tax competition lead to a lowering of tax revenues and to suboptimal levels of public goods and social policies? This paper examines the impact of tax competition on tax structures and social policy financing in the European Union from 1980 to 1997. The expectations of tax structure development are deduced from a simple model of economic integration. The model consists of two countries, each applying two kinds of taxes to finance a public good and a governmental social policy transfer. A market of social insurance is included in the model as an alternative way to finance the social policy transfer. The tax base related to the two taxes are mobile and immobile respectively. In contradiction to expectation the average share of corporate and capital taxation in the EU tax structure has increased from 1980 to 1997, the excise duty share has been constant and the labour income tax share has decreased. Less surprising but evident is the gradual convergence in the tax structures among EU member countries. But the findings show no impact from tax competition on social policy financing.
Keywords: 330; Steuerwettbewerb; Steuersystem; EU-Steuerrecht